Application of Index of Atmospheric Purity (IAP) along elevation gradients in Gunung Jerai, Kedah, Malaysia - Rosli, Nur Syuhada; Zulkifly, Shahrizim (Springer Nature, 2022)
The utilisation of biological organisms, especially lichens in the environmental biomonitoring approach, has been proven to be an effective and low-cost technique suitable for developing countries like Malaysia. Index of Atmospheric Purity (IAP) tracked compositional changes in lichen communities which correlate with changes in levels of atmospheric pollution. Gunung Jerai was formed during the Cambrian Period; thus, it is a biodiversity hotspot ideal for a diverse range of lichens. In the present work, a total of 44 corticolous lichen species were sampled and identified to evaluate the pollution status of Gunung Jerai using IAP, starting from 80 to 1200 m with 300 m intervals. The samples were collected within 10 × 50 cm sampling grids attached to 60 trees, bringing a total of 120 000 cm2 of the sampling area. The air quality of the sampling area was determined by IAP score, a low score indicated by high levels of pollution. Results showed that the lowest IAP score was recorded at 300 m; meanwhile, the highest IAP score was recorded at 900 m elevation. Elevational gradient and pollution have a significant effect on the IAP score of Gunung Jerai. On average, Gunung Jerai is indicated as having a low pollution status. However, several elevations of the rainforest showed high and moderate pollution status. The IAP method is best to assess environmental pollution and provide quicker results than chemical monitoring methods. Further research could be done to evaluate the other sampling sites adjacent to other areas of Gunung Jerai.